Uncovering process-structure relationships associated to the hot isostatic pressing of the high-speed steel PMHS 3-3-4 through novel microstructural characterization methods. (October 2021) - Benito, Santiago; Boes, Johannes; Matsuo, Michele; Weber, Sebastian; Theisen, Werner
Graphical abstract: Highlights: Novel stereology methods and data analysis revealed new process-structure links. The powder solidification has an enduring effect on the final microstructure. Dendritic solidificationof massive particles produces slightly elongated carbides. Cellular solidification is responsible for smaller, more angular carbides. Longer times in the hot isostatic press cause carbide coarsening and rounding. Abstract: Gaining insight into the many agents that determine the underlying material microstructure is essential to engineer new and efficient solutions. Tool steels resistant to abrasive wear are particularly interesting because it is possible to tailor their macroscopic properties by adjusting some of the primary carbide phase features: micromechanical properties, volume fraction, size, and shape. For many popular ledeburitic cold-work and high-speed tool steel alloys, there is a generally good understanding of the effects of the HIP temperature, pressure, and holding time on these traits. Nevertheless, there is still no thorough investigation on the influence of powder size distribution on the primary carbide phase. To that end, we employ in this work novel microstructural characterization methods that shed light on the nature and extent of its influence. We show that powder size has an enduring effect on primary carbide geometric features associated with the solidification process during powder atomization. This work contributes significant process-structure links, which uncover new opportunities for microstructural design.